TRANSFORMASI MEDIA YOUTUBE DAN TELEVISI (ANALISIS FUNGSI DAN KONSUMSI MEDIA YOUTUBE DAN TELEVISI DI KOTA PADANG) - Alna Hanana; Annisa Anindya; Novi Elian (Jurusan Ilmu Komunikasi Universitas Andalas, 2020)
If we talk about television as mass media, what is meant by watching TV is watching programs that are broadcast by television stations. It's just that, seeing the arrival and influence of new media technology at this time, making many functions of the mass media that began to be seized by new media. This research was conducted to see how the process of transformation of functions and consumption of television and Youtube media is carried out by the people of Padang City. In order to examine the changes in this communication media, of course data is needed on how the actual process takes place in the field. To examine the problem, this study uses MediaMorphosis Theory. The study was designed using a quantitative and qualitative mixed approach that was shaded by a post-positiveist paradigm. The quantitative approach is carried out through an explanatory research survey research design to find out the situation or condition that occurs and the factors influencing it. While the qualitative approach is used to explain the variables studied in more detail. The results revealed that the majority of respondents are more concerned with the content presented than the media platform used. The platform only functions as a tool that makes it easy for them to access the content they want, without them really caring about the conceptual differences from the available media choices.